Evaluation of food additives on the rheologic properties of winter wheat flours - Sipos Péter; Győri Zoltán (2012)
The effects of different flour additives on the Farinograph. Alveograph and Extensograph properties of BL 80 flour were evaluated. The purpose of the study was to evaluate the way and degree of their influences to establish a subsequent research on their possible substitution by natural ingredients. We found that the effects of flour additives can be measured by rheologic methods and the extends of changes determined by different methods are similar.